Plant Metabolic Engineering Strategies for the Production of Pharmaceutical Terpenoids - Lu, Xu; Tang, Kexuan; Li, Ping (Frontiers in Plant Science, 2016)
Pharmaceutical terpenoids belong to the most diverse class of natural products. They have significant curative effects on a variety of diseases, such as cancer, cardiovascular diseases, malaria and Alzheimer’s disease. Nowadays, elicitors, including biotic and abiotic elicitors, are often used to activate the pathway of secondary metabolism and enhance the production of target terpenoids. Based on Agrobacterium-mediated genetic transformation, several plant metabolic engineering strategies hold great promise to regulate the biosynthesis of pharmaceutical terpenoids. Overexpressing terpenoids biosynthesis pathway genes in homologous and ectopic plants is an effective strategy to enhance the yield of pharmaceutical terpenoids. Another strategy is to suppress the expression of competitive metabolic pathways. In addition, global regulation which includes regulating the relative transcription factors, endogenous phytohormones and primary metabolism could also markedly increase their yield. All these strategies offer great opportunities to enhance the supply of scarce terpenoids drugs, reduce the price of expensive drugs and improve people's standards of living.